Memorandum on the Beveridge Report - Beveridge, William Henry Beveridge, Baron, 1879-1963 (London : Communist Party of Great Britain)
1943-02 1943 1940s 28 pages Published by the Communist Party of Great Britain, 16 King Street, London, W.C.2, and printed by Langley and Sons, Ltd., The Euston Press, London, N.W.1. CP/B/36/2/43 15X/2/103/272